From Initial Education to Portuguese L1 Classroom: conceptions about teaching and learning grammar - Cardoso, Adriana; Pereira, Susana; Leite, Teresa; Silva, Encarnação (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The goal of this paper is to discuss representations about grammar teaching of Portuguese L1 teachers. It draws on the exploratory study designed to identify the invariants and divergences in self-perceptions about L1 grammar teaching of trainees in different training situations: in-service teachers, pre-service teachers and bachelor’s students. The study focus on student’s and teacher’s acknowledgment of the Portuguese L1 Curriculum (Reis et al. 2009), which conveys a clear paradigm change in Portuguese language education, assuming that grammar teaching is based upon language awareness development. The results show an evident gap between students and teachers in what concerns the familiarity with the Portuguese L1 Curriculum and teaching strategies. However, some puzzling convergent points are the importance attributed to grammar and poor linguistics background. The results analysis draws attention to the relationship between teacher cognition and practice, highlighting fragilities in teacher education and potential conceptual changes that may lead to effective changes in classroom practices.